Table_1_A Temporally Dynamic Gut Microbiome in Atlantic Salmon During Freshwater Recirculating Aquaculture System (RAS) Production and Post-seawater Transfer.XLSX - Marlene Lorgen-Ritchie; Michael Clarkson; Lynn Chalmers; John F. Taylor; Herve Migaud; Samuel A. M. Martin (2021)
Atlantic salmon aquaculture is undergoing an expansion of land-based recirculating aquaculture systems (RAS), especially for freshwater (FW) stages of production. Juvenile salmon undergo parr-smolt transformation, also known as smoltification and become pre-adapted to tolerate seawater (SW). One aspect requiring study is the development of microbial communities during this time, especially in RAS systems. Here we analyzed temporal changes in microbiome associated with the intestine in Atlantic salmon during smolt production in a commercial RAS production facility and followed the same cohort of fish post-seawater transfer (SWT), using 16S rRNA gene sequencing. Microbial diversity and richness showed an increase over time across FW production, but declined sharply and significantly 1-week post-SWT before re-establishing itself with a completely different community structure after 4 weeks. Core microbial taxa could be assigned to three distinct categories; (1) omnipresent, (2) salinity specific, or (3) transient. By including diet and water samples in the analyses, we classified true core taxa associated with the host, those associated with the diet, and transient cores associated with microbial communities in tank water. The rising trend observed in microbial richness in the water may be a consequence of a temporal increase in organic load while dominance of Vibrionaceae may be attributed to the higher temperatures maintained during RAS production and above average natural water temperatures post-SWT. Functional analysis suggests modulation of metabolic pathways post-SWT, but downstream impacts on fish growth and health in a commercial setting remain to be elucidated. A deeper understanding of the interplay between microbial composition and functionality can play a role in optimizing fish performance in tightly regulated RAS production.